2013
DOI: 10.4103/0974-8237.121627
|View full text |Cite
|
Sign up to set email alerts
|

Giant posterior fossa arachnoid cyst causing tonsillar herniation and cervical syringomyelia

Abstract: Acquired cerebellar tonsillar herniation and syringomyelia associated with posterior fossa mass lesions is an exception rather than the rule. In the present article, we describe the neuroimaging findings in a case of 28-year-old female patient presented with a history of paraesthesia involving right upper limb of 8-month duration. Magnetic resonance imaging showed a giant retrocerebellar arachnoid causing tonsillar herniation with cervical syringomyelia. The findings in the present case supports that the one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A literature review found only 7 cases having such a rare association [1,2,3,5,6,7,8,9]. All reported cases are adults, and ours is the first such reported case in a child.…”
Section: Figmentioning
confidence: 87%
See 1 more Smart Citation
“…A literature review found only 7 cases having such a rare association [1,2,3,5,6,7,8,9]. All reported cases are adults, and ours is the first such reported case in a child.…”
Section: Figmentioning
confidence: 87%
“…This might either be because of direct obstruction at the foramen magnum level by the cyst itself as in the majority of cases or rarely lead to a secondary tonsillar herniation and resultant syrinx [1,4]. The latter mechanism is extremely rare, and till now, only a handful of such cases have been reported in the English literature [1,2,3,5,6,7,8,9]. Although the exact aetiopathogenesis of syringomyelia is controversial, many hypotheses have been postulated but the one suggested by Ball and Dayan [10] combined with others would be most appropriate in our case.…”
Section: Figmentioning
confidence: 99%
“…Posterior fossa arachnoid cysts represent roughly one fourth of all these congenital pouches. There have been several other reports that have noted large arachnoid cysts associated with syringomyelia 9 18) .…”
Section: Discussionmentioning
confidence: 98%
“…Various surgical options exist for the treatment of retrocerebellar arachnoid cyst according to the underlying pathogenic mechanism, including cyst fenestration, cyst-peritoneal shunting, and foramen magnum decompression with complete or partial excision 1 4 15) . Removal of the underlying pathology and stablishing the normal CSF flow at the foramen magnum is the main stay of treatment for syringomyelia 9) . For cases of foramen magnum arachnoid cyst with direct compression of the spinal cord and syringomyelia, excision should be performed as much as possible with complete decompression of the posterior fossa, which should result in a satisfying outcome even if the arachnoid cyst is unable to be completely excised 7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation